The preventive effect of probiotic Lactobacillus plantarum X86 isolated from raw milk on Staphylococcus aureus-induced mastitis in rats - Xie, Xiulan; Cao, Mei; Yan, Shiying; Gao, Haihui; Yang, Yuwei; Zeng, Jiayi; Zhang, Gang; Zhao, Jian (Frontiers in Veterinary Science, 2025)
Mastitis is the most common and challenging disease that affects dairy animal welfare and causes huge economic loss in dairy industry globally. Conventional antibiotic treatment of mastitis raised the drug resistance and unsuccessful therapy. As an alternative approach, probiotic lactobacilli had shown multifunctional effects against diseases. Lactobacillus strains against mastitis are worth screening and evaluating. In this study, milk-derived Lactobacillus spp. from Ningxia, China were screened in vitro and the anti-mastitis effect of a candidate strain was evaluated through a Staphylococcus aureus-induced rat mastitis model. The results showed that Lactobacillus plantarum X86 exhibited a high adhesion rate of MAC-T cells, presented the best probiotic properties, and demonstrated anti-S. aureus effects in vitro through comprehensive assessment. Furthermore, L. plantarum X86 alleviated pathological damage to the mammary gland, liver, and colon, inhibited the mRNA expression of pro-inflammatory cytokines factors IL-1β, IL-6, and TNF-α in mammary gland tissue; and increased the content of intestine SCFAs in a rat mastitis model induced by S. aureus. In conclusion, our results suggested that L. plantarum X86 could be a promising probiotic for the prevention and treatment of S. aureus-induced mastitis.